2017
DOI: 10.18203/2320-6012.ijrms20173568
|View full text |Cite
|
Sign up to set email alerts
|

Positioning for regional anesthesia in femur fracture surgeries: how effective is femoral nerve block? a randomised control study

Abstract: Background: Fracture of the femur is a common orthopaedic problem following trauma in patients of all ages. This study was undertaken to evaluate the effectiveness of femoral nerve block (FNB) in positioning the patients for regional anesthesia.Methods: 100 patients between the ages 18 to 80 years, of ASA grade I, II and III, scheduled for elective surgeries of femur fracture were evaluated in 2 groups. Group FNB (n=50) received femoral nerve block with 15ml of 1.5% lignocaine and Group. Non FNB (n=50) was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
6
2
0
1
Order By: Relevance
“…The present study shows that FNB and FICB were effective in reducing pain during positioning than IVFE [median (IQR)]; 2(1–2.5), 2(2–3)) vs. 3(3–4) respectively, which is comparable with recent studies done by Purohit et al, 17 comparing placebo-controlled FNB that showed VAS score of (mean± SD (8.25±0.36,1.47±0.16)) respectively and Hsu et al, 16 comparing FNB and intravenous opioids. Madabushi et al, 13 which compares FICB to IVFE also showed similar results to the present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study shows that FNB and FICB were effective in reducing pain during positioning than IVFE [median (IQR)]; 2(1–2.5), 2(2–3)) vs. 3(3–4) respectively, which is comparable with recent studies done by Purohit et al, 17 comparing placebo-controlled FNB that showed VAS score of (mean± SD (8.25±0.36,1.47±0.16)) respectively and Hsu et al, 16 comparing FNB and intravenous opioids. Madabushi et al, 13 which compares FICB to IVFE also showed similar results to the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study quality of positioning was higher in patients with FNB or FICB 2(2-3) for both groups than IVFE 2(1-2) which is also comparable to previous studies by Purohit et al, 17 (2.8±1.3, 1.4±0.2), Madabushi et al, 13 (2.06±078, 1.25±0.85) and Hsu et al 16 This study shows that patient acceptance was greater in patients with FNB and FICB than IVFE (87.5%, 79%, and 41.7%) respectively. This is in line with previous studies done by Purohit et al, 17 (90%, 20%) for FNB vs. non FNB groups and Hsu et al, 16 also showed regional nerve blocks provide greater patient acceptance than intravenous opioids.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Саме тому у вітчизняній практиці при знеболюванні перед операцією на нижніх кінцівках віддають перевагу методам регіонарної анестезії. Одним із найпоширеніших із них є спинномозкова анестезія, яка має такі очевидні переваги, як простота та швидкість виконання, надійне знеболювання [10,11].…”
unclassified